2016
DOI: 10.1038/srep33044
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends of Summer Convective and Stratiform Precipitation in Mid-Eastern China

Abstract: Many studies have reported on the trends of precipitation in Mid-Eastern China (EC). However, the trends of convective and stratiform precipitation are still unknown. Here, we examine the trends of summer convective and stratiform precipitation in EC from 2002 to 2012 on the basis of the TRMM observations. Results revealed that the rain frequency (RF) for both convective and stratiform precipitation increased in majority regions of Southern EC (SEC), but decreased in Northwest part of Northern EC (NEC). The de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…Our experimental rain addition simulates larger but less frequent rain events rather than a regular, small increase in rainfall. While this matches the local inhabitants’ perceptions of climate change (Singh et al., 2015; informal accounts of residents of Kibber, Spiti) and observed trends of increasing frequency and magnitude of large storm events (Fu et al., 2016; Goulden et al., 2016), it leaves room to explore how other modes of precipitation increase may impact vegetation. One shortcoming of our study is a lack of soil moisture data; linking changes in soil moisture to changes in vegetation would provide a clearer understanding of mechanisms underlying vegetation responses to climate and grazing.…”
Section: Discussionsupporting
confidence: 73%
“…Our experimental rain addition simulates larger but less frequent rain events rather than a regular, small increase in rainfall. While this matches the local inhabitants’ perceptions of climate change (Singh et al., 2015; informal accounts of residents of Kibber, Spiti) and observed trends of increasing frequency and magnitude of large storm events (Fu et al., 2016; Goulden et al., 2016), it leaves room to explore how other modes of precipitation increase may impact vegetation. One shortcoming of our study is a lack of soil moisture data; linking changes in soil moisture to changes in vegetation would provide a clearer understanding of mechanisms underlying vegetation responses to climate and grazing.…”
Section: Discussionsupporting
confidence: 73%
“…Beyond the summer seasonal mean (until 30 °C), hourly precipitation extremes continue to intensify at a sub-C-C rate while daily precipitation extremes decrease rapidly with rising temperatures. We have inferred that it is probably the extreme convective summer rainfall continues to intensify, but further investigation such as refs 19,20,34 are urgently needed to confirm that.…”
Section: Discussionmentioning
confidence: 88%
“…A survey by the residential development department in China has found that 62% of cities were flooded at least once between 2008 and 2010, based on a sample of 351 Chinese cities (http://news.ifeng.com/shendu/nfzm/detail_2013_07/18/27643337_0.shtml). During the period 1971–2013, the regional average summer mean temperature across a large part of China has increased by ~0.95 °C, smaller than the annual mean rise of 1.44 °C34, but the regionally averaged maximum summer hourly precipitation has increased by 11.2%. Using various different measures, we have shown that hourly and daily summer precipitation extremes in China increase robustly at super-C-C scalings with rising temperatures.…”
Section: Discussionmentioning
confidence: 94%
“…2f). The trends of the different types of precipitation are caused by changes in their frequency and intensity throughout China, but their changes are not completely consistent in space and time (Fu et al 2016;Han et al 2016). The 9-year moving averages of the different precipitation anomalies show interdecadal characteristics.…”
Section: Spatial and Temporal Characteristics Of Annual Precipitationmentioning
confidence: 99%